Caribbean Energy : Macro-Related Challenges - McIntyre, Arnold (IMF Working Papers; Working Paper ;, 2016)
High energy costs contribute to dampening Caribbean competitiveness and potential growth. This paper overviews power sector challenges and takes stock of national and regional strategies to address them. It presents recommendations to move the energy agenda forward based on analyses of macro-aspects of energy reform. These include: i) quantitative assessment of the impact of energy costs on growth and competitiveness; ii) evaluation of gains from implementing announced renewable energy and energy efficiency targets; and iii) analysis of the impact of energy investments on debt sustainability. The paper argues for a bigger role for the private sector in energy reform and discusses prerequisites for good public-private partnerships.